IMPACT OF ISLAMIC BANKING INCLUSION ON SME EMPLOYMENT GROWTH IN NIGERIA - Tasiu Tijjani Sabiu; Muhamad Abduh (Journal of Islamic Monetary Economics and Finance, 2021)
Despite the considerable resources devoted to SMEs by Islamic banks worldwide, and Nigeria in particular, there has been no rigorous empirical evidence regarding the effectiveness of Islamic banking inclusion on employment growth in SMEs globally. This study fills this gap by analysing the effectiveness of access to Islamic banking financing in promoting MSME's growth in Kano Metropolis, Nigeria. We focus on the impact of the credit lines facilitated by Jaiz Bank Plc in fostering firms’ growth measured in terms of employment. A survey based on a quasi- experimental approach was employed and the data were collected by means of a questionnaire distributed to a sample of 385 MSMEs' beneficiaries and non-beneficiaries of Islamic bank financing in Kano Metropolis, Nigeria. Using difference-in-difference and propensity score matching techniques to deal with selection bias, the study found significant positive effects on MSMEs’ employment growth. In addition, the paper highlights the important role of Islamic bank financing in mitigating the unemployment crisis in Nigeria. The paper recommends that improvement of the Islamic banking system by employing PLS financing, especially Musharaka, could foster MSMEs' financial inclusion and job creation.